Incidence of Hypertension in Adolescents in the Working Areas of Paccerakkang Health Center and Sudiang Health Center in Makassar City - Hasliani, Hasliani (Journal of World Future Medicine, Health and Nursing, 2024)
Hypertension generally occurs in the elderly, but several studies have shown that hypertension can appear as early as adolescence and its prevalence has increased over the past few decades. However, many have not realized that this is the cause of the appearance of hypertension in adulthood and the elderly. This study aims to determine the prevalence of hypertension in adolescents at the Sudiang Raya Health Center, Makassar City. The method used was observation with a Cross Sectional approach. The study sample was 147 adolescents using Two Stage Cluster Sampling. Data collection using questionnaires, measurement of weight, height and blood pressure. Data were analyzed univariately using frequency distribution tables. The results showed that there were 73 male respondents (49.7%) and 74 female respondents (50.3%). Most (77.6%) respondents had a moderate level of knowledge. The results of blood pressure measurements showed that 9 people (6.1%) were categorized as stage 2 hypertension, 18 people (12.2%) were categorized as stage 1 hypertension, 22 people (15.0%) were categorized as pre-hypertension and 98 people (66.7%) had normal blood pressure. Closing: The results showed that one third of respondents already had hypertension.